PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS X SMA NEGERI 9 PADANG - Qisty, Husna Bil (Jurnal Edukasi dan Penelitian Matematika, 2024)
One of the most valuable skills is the ability to solve problems. However, initial assessments and classroom observations showed that students in grade X at SMA Negeri 9 Padang had low levels of this ability. The Problem Based Learning (PBL) approach was used in an attempt to hone this skill. Learners' progress in this area was detailed, and compared with learners using the direct learning approach and PBL methodology. The study was descriptive in nature and was conducted as a quasi-experiment. Sampling was done randomly. Two classes, X 8 and X 7, were used as samples. Non-Equivalent Posttest Only Control Group Design was the research design used in this study. The PBL methodology improved all measures of problem-solving ability, as indicated by the quiz and final test results. The results showed that problem-based learning (PBL) was more effective than direct learningKeywords– Problem Based Learning, Direct learning, Mathematical Problem Solving Abilities